Compressive performance evaluation of concrete confined by stirrups at elevated temperature using DIC technology. (10th November 2020) - Liu, Yanhua; Zeng, Lei; Xiang, Sheng; Mo, Jinxu; Zhang, Jicheng; Chen, Juan; Cheng, Guoyuan
Highlights: The residual mechanical properties of stirrup confined concrete were discussed. Monitoring of cracks distribution and development using DIC technology. Effects of stirrup ratios and temperatures on stress-strain response. The usefulness of DIC method for strain measurement in compression test. Abstract: This paper focuses on the effects of high temperatures on the physical and mechanical properties of concrete confined by stirrups. Axial compression tests on a total of 20 specimens were carried out, and the main experimental parameters including exposure temperatures and stirrup ratios were considered. The cubes were heated at specified temperatures ranging from 200 °C to 600 °C. The development process of the observed surface displacement was quantitatively and vividly described by the Digital Image Correlation (DIC) technique. Under the displacement-controlled loading scheme, the stress-strain behavior and residual bearing capacity of the specimen were measured while the failure mode was observed. The results show that the mass loss increases with the increase of temperature. The compressive strength and Young's modulus deteriorated sharply after 400 °C. However, the average reduction of elastic modulus at elevated temperatures was greater than that of compressive strength. Results further showed that stirrups can improve ductility of concrete under high temperature environment. The tracking test of crack propagation verified the advantages of the DIC technology for its real-time, dynamic and non-contact measurement.